PENGEMBANGAN SUMBER DAYA MANUSIA DI INSTITUT AGAMA ISLAM NEGERI (IAIN) BENGKULU MELALUI PENDEKATAN MOTIVASI - Syaifuddin, Syaifuddin (Institut Agama Islam Bengkulu, 2018)
Human Resources development has an important role in improving employee performance and productivity. In developing human resources, it can be done using a work motivation approach where work motivation is an impulse to do something consciously that arises from within and outside of each individual with the aim of increasing superior and competitive human resources. In the work motivation there are 6 motivational theories including: Need theory from Abraham Maslow, (b) Frederick Herzberg's two-factor theory, (c) McClelland's Achievement Theory, (d) Strengthening Theory (e ) Expectancy Theory, (f) Purpose Theory as Motivation. Based on this theory a leader can do various things to improve employee motivation and work to improve work productivity because with high motivation, work productivity will also be high and vice versa because between the two will be interrelated.